ANALISIS PENGARUH MARKETING MIX (7P) TERHADAP KEPUASAN KONSUMEN MELALUI LOYALITAS KONSUMEN (Studi Kasus pada Klinik Kecantikan Larissa Aesthethic Center Di Semarang) - Nur Jayanti, 09.05.51.0034; Kasmari, Kasmari (Students Journal of Economic and Management, 2013)
This research analyzes the influence of the marketing mix 7P to customer satisfaction through customer loyalty. Total Samples in this research were 100 respondents. Technique sampling of this research is purposive accidental sampling. Analysis data in use is multiple regression model. The result of this reseacrh shown that variable product, price, process, personal positive and significant impact on customer satisfaction while variable promotion, place physical evidence of a positive and not significant impact on customer satisfaction. Simultaneous testing 7P also a positive and significant impact on customer satisfaction. And satisfaction also affects customer loyalty.Key words: Product, Price, Promotion, Place, Process, Personal, Physical Evidence, Satisfaction dan Customer Loyalty.